Relationship between BMI and β-hCG levels with hyperemesis gravidarum in Manado, Indonesia - Inne Mamesah; Maria Loho; Eddy Suparman (Majalah Obstetri dan Ginekologi, 2019)
Objectives: The main objective of this study was to determine the relationship between BMI and β-HCG levels with hyperemesis gravidarum.Materials and Methods: This study was a case control study which compares between BMI and β-Hcg levels of patients with hyperemesis gravidarum and without hyperemesis gravidarum. This study was conducted at Obstetric and Ginecology Department of Medical  Faculty of Sam Ratulangi University in Manado. This study was conducted on September - November 2018 and participated by 33 pregnant women with hyperemesis gravidarum and 33 pregnant women without hyperemesis gravidarum which were included in accordance to the inclusion criteria and signed the informed consent to participate in this study.Results: The percentage of patients with Hyperemesis Gravidarum within the age group of 20 -35 years old were 23 patients (69.69%). The highest number of patients without Hyperemesis Gravidarum were [VL1] within age group of 20 - 35 years old as many [VL2] as 28 patients (84.84%). Hyperemesis Gravidarum was found the most in normal BMI group, which was 26 patients (78.78%). The patients without hyperemesis gravidarum were also found in the highest number in the normal BMI group, 21 patients (63.63%). T-test showed that there was no significant difference in BMI of group with postive HEG and negative HEG (p = 0.027). Spearman Correlation Test had been conducted to show relationship between β-hCG levels, and there was a strong correlation between gestational age and β-Hcg levels (r = 0,764 ; p = 0,000), which means β-hGG level increased along with gestational age.Conclusion:There was significant relationship between β-hCG and Hyperemesis Gravidarum. There was also a significant relationship between gestational age and β-hCG Levels which mean the increase of β-hGG level is along with the increase of gestational age. Tere was no significant relationship between BMI and Hyperemesis Gravidarum.